Differential Expression of Dopamine D5 Receptors across Neuronal Subtypes in Macaque Frontal Eye Field - Mueller, Adrienne; Shepard, Steven B.; Moore, Tirin (Frontiers in Neural Circuits, 2018)
Dopamine signaling in the prefrontal cortex (PFC) is important for cognitive functions, yet very little is known about the expression of the D5 class of dopamine receptors (D5Rs) in this region. To address this, we co-stained for D5Rs, pyramidal neurons (neurogranin+), putative long-range projection pyramidal neurons (SMI-32+), and several classes of inhibitory interneuron (parvalbumin+, calbindin+, calretinin+, somatostatin+) within the frontal eye field (FEF): an area within the PFC involved in the control of visual spatial attention. We then quantified the co-expression of D5Rs with markers of different cell types across different layers of the FEF. We show that: (1) D5Rs are more prevalent on pyramidal neurons than on inhibitory interneurons. (2) D5Rs are disproportionately expressed on putative long-range projecting pyramidal neurons. The disproportionately high expression of D5Rs on long-range projecting pyramidals, compared to interneurons, was particularly pronounced in layers II–III. Together these results indicate that the engagement of D5R-dependent mechanisms in the FEF varies depending on cell type and cortical layer, and suggests that non-locally projecting neurons contribute disproportionately to functions involving the D5R subtype.